Development of a Novel Bronchodilator Vaping Drug Delivery System Based on Thermal Degradation Properties - Mariam Chaoui; Emmanuelle Fischer; Sophie Perinel-Ragey; Nathalie Prévôt; Lara Leclerc; Jérémie Pourchez (MDPI AG, 2023)
This work aims to investigate bronchodilator delivery with the use of different vaping drug delivery systems (VDDS) by determining the dose equivalence delivered in relation to different references: a clinical jet nebulizer, a pMDI (pressurized metered dose inhaler) and a DPI (dry powder inhaler). Three different bronchodilators were used (terbutaline, salbutamol hemisulfate, ipratropium bromide). The e-liquids contained the active pharmaceutical ingredient (API) in powder form. Two different VDDS were tested (JUUL and a GS AIR 2 atomizer paired with a variable lithium-ion battery (i-stick TC 40 W), 1.5 ohm resistance, and 15 W power). Samples were collected using a glass twin impinger (GTI). High-performance liquid chromatography (HPLC) was used to quantify the drugs. A next-generation impactor (NGI) was used to measure the particle size distribution. Terbutaline emerged as the optimal API for bronchodilator delivery in both VDDS devices. It achieved the delivery of a respirable dose of 20.05 ± 4.2 µg/puff for GS AIR 2 and 2.98 ± 0.52 µg/puff for JUUL. With these delivered doses, it is possible to achieve a dose equivalence similar to that of a jet nebulizer and DPI, all while maintaining a reasonable duration, particularly with the GS AIR 2. This study is the first to provide evidence that vaping bronchodilators work only with appropriate formulation, vaping technology, and specific drugs, depending on their thermal degradation properties.